Systematic development of a device for bituminous layer application - Benedičič, Janez (Strojniški vestnik, 2013)
A method has been developed that enables a systematic approach to searching for opportunities to design new products by taking account of the relevant business environments. The process of searching for opportunities involves the already recognized social, economic, technological and legislative factors (SETL) through which outside influences are measured, and the use of the SETL factors makes it even more systematic. The industrial application of this method as described below has resulted in an innovative product that has already increased existing productivity by a factor of 3, as well as knowledge transfer. The new product has also expanded a developing product family in the company's existing product portfolio.
Keywords: academic-industrial team; competitive products; delovni proces; industrial case; industrijska uporaba; inovacija; iskanje priložnosti; methodology; metodologija; productivity; produktivnost; razvoj novega izdelka; training of product developers